Justification of the calculation methods of the main parameters of vortex chambers - Pitak, Inna; Shaporev, Valery; Briankin, Serhii; Pitak, Oleg (Technology audit and production reserves, 2017)
The object of research is vortex dust collectors – apparatus in which hydrodynamic regimes are realized. Advantages of using vortex apparatus: work with gases of high temperature, high degree of purification; regulation of the process of gas cleaning from dust due to regulating the secondary air flow. Among the disadvantages of vortex dust collectors are: high hydraulic resistance, the need for powerful blowing apparatus, as well as difficult operation and installation. Apparatus for swirling the flow have a different design and, depending on the gas flow rate, pressure and physicochemical properties of the gas flow at the inlet to the cleaning apparatus, this or that hydrodynamic regime is created in it. When designing vortex chambers, the following design parameters must be observed: Ds/D»0.8; Di/Ds»0.5; Dw/D»0.5¸0.8; the inclination angle of the vortex blades at the inlet of the main flow is b»30¸60º; the inclination angle of the secondary flow nozzles is a»30¸45º. When calculating and designing a vortex chamber, it is necessary to fulfill the conditions for the constancy of the tangential velocity of the total flow along the entire length of the working cavity of the apparatus, ensuring the maximum possible efficiency of its functioning. Analysis of the obtained results for justification of the methods for calculating the basic parameters of the vortex chambers indicates the expediency of using such methods for calculating gas cleaning equipment. When implementing the process of cleaning dust-gas flows in vortex apparatus, not only the processes of agglomeration of dust are observed, but also the destruction of gas toxicants. Mathematical dependencies are considered to allow make predictive estimations to select the conditions of the dry dust removal process and to select the design parameters of the vortex chamber. This opens prospects for the introduction of vortex apparatus in order to reduce the industrial negative impact on the environment, namely the atmosphere.